There's something happening here : the New Left, the Klan, and FBI counterintelligence - Cunningham, David, 1970- (Berkeley : University of California Press, 2004)
Cunningham explores the FBI's COINTELPROs against white hate groups and the New Left to examine how agents dealt with the hundreds of individuals and organizations labelled as subversive threats. The author focuses on the complex organizational dynamics which generated the thousands of COINTELPRO actions.
Counterintelligence activities and the FBI -- The movements -- The organization of the FBI : constructing white hate and new left threats -- Acting against the white hate and new left threats -- Wing tips in their midst : the impact of COINTELPRO -- Beyond COINTELPRO -- The future is now : counter/intelligence activities in the age of global terrorism.
Includes bibliographical references (pages 343-356) and index.
Print version record.
JSTOR
Keywords: United States. -- Federal Bureau of Investigation; Cointelpro; États-Unis. -- Federal Bureau of Investigation; United States. -- Federal Bureau of Investigation; USA -- Federal Bureau of Investigation; United States. -- Federal Bureau of Investigation; USA / FBI; Intelligence service -- United States; New Left -- Government policy -- United States; Hate groups -- Government policy -- United States; Nouvelle gauche -- Politique gouvernementale -- États-Unis.; Groupes haineux -- Politique gouvernementale -- États-Unis.; LAW -- Forensic Science; HISTORY -- United States -- General; Hate groups -- Government policy; Intelligence service; United States; Unterdrückung; Überwachung; Rechtsradikalismus; Neue Linke; FBI; Burgerrechten; Onderdrukking; New Left; Ku Klux Klan; Intelligence service -- United States; New Left -- Government policy -- United States; Hate groups -- Government policy -- United States; Services de renseignements -- États-Unis.; Gauche (science politique) -- États-Unis.; Racisme -- Politique publique -- États-Unis.; Discrimination raciale -- Politique publique -- États-Unis.; Discours de haine -- Politique publique -- États-Unis.